Clinicopathological features and pituitary homeobox 1 gene expression in the progression and prognosis of cutaneous malignant melanoma. Issue 10 (27th August 2016) - Barut, Figen; Udul, Perihan; Kokturk, Furuzan; Kandemir, Nilufer Onak; Keser, Sevinc Hallac; Ozdamar, Sukru Oguz
Abstract: The evidence that PITX1 (pituitary homeobox 1) is a significant tumor suppressor in human cancer remains largely circumstantial, but it clearly warrants further study as little is known about the tumor‐inhibitory roles of PITX1 in cutaneous malignant melanoma. The aims of this study were to investigate PITX1 gene expression in patients with cutaneous malignant melanoma and to evaluate its potential relevance to clinicopathological characteristics and tumor cell proliferation. Clinicopathological findings of patients with cutaneous malignant melanoma were analyzed retrospectively. PITX1 and Ki‐67 expression were detected by immunohistochemistry in malignant melanoma and healthy tissue samples from each patient. Labeling indices were calculated based on PITX1 gene and Ki‐67 expression. The correlation between PITX1and Ki‐67 expressions was analyzed in cutaneous malignant melanoma cases. The relationship between PITX1 expression intensity and clinicopathological characteristics was also analyzed. PITX1 expression was observed in all (100%) normal healthy skin tissue samples. In addition, PITX1 expression was found in 56 (80%) and was absent in 14 (20%) of the 70 cutaneous malignant melanoma cases. Ki‐67 positive expression was only detected in the 14 (20%) PITX1‐negative cases. PITX1‐positive tumor cells were observed on the surface, but Ki‐67 positive tumor cells were observed in deeper zones of the tumor nests. PITX1 expression was downregulated in human cutaneous malignant melanoma lesions compared with healthy skin tissue, but Ki‐67 expression was upregulated in concordance with the progression of cutaneous malignant melanoma. PITX1 expression may be involved in tumor progression and is a potential tumor suppressor gene and prognostic marker for cutaneous malignant melanoma.